THE INFLUENCE OF ORGANIZATIONAL CULTURE TOWARDS EMPLOYEE’S PERFORMANCE OF MILLENNIALS GENERATION IN PT. JASA RAHARJA NORTH SUMATERA BRANCH - Siti Safira Mayhara; Yeni Absah; Amlys Syahputra Silalahi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This study uses research variables such as organizational culture and employee’s performance. The purpose of this study was to determine the effect of organizational culture towards employee’s performance to employee of millennial generation of PT Jasa Raharja North Sumatera branch. The approach used in this study is an associative approach and the population in this study are generation “Y” employees of PT Jasa Raharja North Sumatra branch. This research uses non probability sampling which sample must fulfil terms and conditions to be respondent. The determination of the sample size in this study was carried out using the Slovin formula. Based on the results of the Slovin formula, the number of respondents used in this study was 69 respondents.Data collection technique in this study used a questionnaire technique. Data analysis techniques in this study use Structural Equation Model (SEM) Partial Least Square (PLS). Data processing in this study using the SmartPLS 3.0 software program. The results show that organizational culture affects toward employees performance millennials generation at PT Jasa Raharja North Sumatera branch.